1985
DOI: 10.1177/002234338502200305
|View full text |Cite
|
Sign up to set email alerts
|

The Economics of Exporting Arms

Abstract: The international trade in arms has an important economic dimension which this paper attempts to examine. After reviewing the evolution of demand and supply, the implications of the current market structure for price and revenue are examined. This suggests that, in purely commercial terms, the promotion of arms exports by a country is not a profitable proposition. Given this, we consider why governments in supplier countries have nonetheless heavily promoted arms exports. It appears that the initial momentum w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

1987
1987
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 2 publications
0
21
0
1
Order By: Relevance
“…Instead, the literature focuses on the effects of their arms transfers (Blanton 2000(Blanton , 2005Sanjian 1999Sanjian , 2001. Of course, a broader literature on arms transfers exists that focuses on United States decision-making from either a historical or qualitative perspective (Hammond et al 1983;Krause 1991;Mott 2002), which is a subset of the general arms transfer decision-making literature (Brauer 1991;Frank 1969;Harkavy 1975;Smith, Humm, and Fontanel 1985). All of the literature agrees upon the broad motivation for exporting arms -security, influence, and economics -which I focus on here.…”
Section: United States Arms Transfer Decision-making: Determinants Ofmentioning
confidence: 92%
“…Instead, the literature focuses on the effects of their arms transfers (Blanton 2000(Blanton , 2005Sanjian 1999Sanjian , 2001. Of course, a broader literature on arms transfers exists that focuses on United States decision-making from either a historical or qualitative perspective (Hammond et al 1983;Krause 1991;Mott 2002), which is a subset of the general arms transfer decision-making literature (Brauer 1991;Frank 1969;Harkavy 1975;Smith, Humm, and Fontanel 1985). All of the literature agrees upon the broad motivation for exporting arms -security, influence, and economics -which I focus on here.…”
Section: United States Arms Transfer Decision-making: Determinants Ofmentioning
confidence: 92%
“…As the Cold War was coming to an end, Smith et al (1985) started working on another issue of wide general interest, namely the arms trade and its wider economic implications. The international trade in arms had received growing interest since the 1980s, and a number of political concerns such as security implications and human rights have attracted a great deal of attention.…”
Section: Scholarly Contributionsmentioning
confidence: 99%
“…Smith has published a series of articles on these issues. Smith et al (1985) suggested that, in purely commercial terms, promoting arms exports is not a profitable proposition. Why then do governments in supplier countries so heavily promote arms exports?…”
Section: Scholarly Contributionsmentioning
confidence: 99%
“…Weapons are often traded as part of a larger package that may include related aspects such as access to technology and spare parts and seemingly unrelated aspects such as offset agreements (Levine, Sen, and Smith 1994, 4; Levine and Smith 1997, 346). In one example from the 1980s, Smith, Humm, and Fontanel (1985, 241) note that the Belgian purchase of military vehicles from Bombardier of Canada was tied to landing rights in Toronto for the Belgian commercial airline, Sabena. Furthermore, the close relationship between arms firms and national governments means that the production and trade of the weapons, not to mention research and development and marketing efforts, are often heavily subsidized by governments and that major international trades are more in line with national priorities than with the profit maximization goals of the private firms (Levine, Sen, and Smith 1994, 4; Smith, Humm, and Fontanel 1985, 242).…”
Section: Analytical Frameworkmentioning
confidence: 99%
“…Historically, unprecedented OPEC oil revenues in the 1970s and 1980s provided an alternative source of finance and much of these petrodollars were spent on importing weapons. Conversely, weapons‐ exporting countries found a means to offset the balance of payments discrepancy that resulted from the higher oil prices (Levine, Sen, and Smith 1994, 3; Smith, Humm, and Fontanel 1985, 240–241). But the period considered in this study, 1989–1999, was an era of relatively low and stable oil prices, and this argument is not very satisfactory 2…”
Section: Introductionmentioning
confidence: 99%